Inhibition of corticosterone synthesis impairs cued water maze consolidation, but it does not affect the expression of BDNF, CK2 and SGK1 genes in dorsal striatum - Pegueros-Maldonado, Rogelio; Pech-Pool, Santiago M.; Blancas, Jaisson J.; Prado-Alcalá, Roberto A.; Arámburo, Carlos; Luna, Maricela; Quirarte, Gina L. (Frontiers in Behavioral Neuroscience, 2024)
Corticosterone (CORT) release during learning experiences is associated with strong memories and activity of the glucocorticoid receptor. It has been shown that lesions of the dorsal striatum (DS) of rats trained in the cued version of the Morris water maze impair memory, and that local injection of CORT improves its performance, suggesting that DS activity is involved in procedural memory which may be modulated by CORT. We trained rats in cued Morris water maze and analyzed the effect of CORT synthesis inhibition on performance, CORT levels, expression of plasticity-involved genes, such as the brain derived neurotrophic factor (BDNF), casein kinase 2 (CK2), and the serum/glucocorticoid regulated kinase 1 (SGK1), as well as the presence of phosphorylated nuclear glucocorticoid receptor in serine 232 (pGR-S232) in the DS. The inhibition of CORT synthesis by metyrapone reduced CORT levels in plasma, prevented its increment in DS and impaired the performance of cued water maze. Additionally, there was an increase of CK2 and SGK1 mRNAs expression in trained subjects, which was unrelated to CORT levels. Finally, we did not observe changes in nuclear pGR-S232 in any condition. Our findings agree with evidence demonstrating that decreasing CORT levels hinders acquisition and consolidation of the spatial version of the Morris water maze; these novel findings broaden our knowledge about the involvement of the DS in the mechanisms underlying procedural memory.